GE_GERICHTE P/20015/2021 vom 16. Februar 2023 - GE Cour de justice (2023)
ABUS D'AUTORITÉ;POLICE;LÉSION CORPORELLE SIMPLE;ASSISTANCE JUDICIAIRE | CPP.310; CPP.136; CEDH.3; CP.312; CP.126; CP.123; CP.31